Health-seeking behaviours by gender among adolescents in Soweto, South Africa - Kennedy Otwombe; Janan Dietrich; Fatima Laher; Stefanie Hornschuh; Busisiwe Nkala; Lucy Chimoyi; Angela Kaida; Glenda E. Gray; Cari L. Miller (Taylor & Francis Group, 2015)
Background: Adolescents are an important age-group for preventing disease and supporting health yet little is known about their health-seeking behaviours. Objective: We describe socio-demographic characteristics and health-seeking behaviours of adolescents in Soweto, South Africa, in order to broaden our understanding of their health needs. Design: The Botsha Bophelo Adolescent Health Study was an interviewer-administered cross-sectional survey of 830 adolescents (14-19 years) conducted in Soweto from 2010 to 2012. Health-seeking behaviours were defined as accessing medical services and/or being hospitalised in the 6 months prior to the survey. Chi-square analysis tested for associations between gender, other socio-demographic and behavioural characteristics, and health-seeking behaviours. Results: Of 830 adolescents, 57% were female, 50% were aged 17-19 years, 85% were enrolled in school, and 78% reported experiencing medium or high food insecurity. Males were more likely than females to report sexual debut (64% vs. 49%; p<0.0001) and illicit drug use (11% vs. 3%; p<0.0001). Approximately 27% (n=224) and 8% (n=65) reported seeking healthcare or being hospitalised respectively in the previous 6 months, with no significant differences by gender. Services were most commonly sought at medical clinics (75%), predominantly because of flu-like symptoms (32%), followed by concerns about HIV (10%). Compared to females, males were more likely to seek healthcare for condom breakage (8% vs. 2%; p=0.02). Relative to males, a significantly higher proportion of females desired general healthcare services (85% vs. 78%; p=0.0091), counselling (82% vs. 70%; p<0.0001), and reproductive health services (64% vs. 56%; p=0.02). Conclusions: A quarter of male and female adolescents accessed health services in the 6 months prior to the interview. Adolescents reported a gap between the availability and the need for general, reproductive, and counselling services. Integrated adolescent-friendly, school-based health services are recommended to bridge this gap.